Ancient Indian economic thought relevance for today - Basu, Ratan Lal (Rawat Publ., 2008)
Economic thought in Arthaśāstra by Kauṭalya and Mānavadharmaśāstra by Manu, two ancient Hindu texts and its relevance in the globalized arena